2020
DOI: 10.3390/antiox9050401
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Modulation of Systemic Inflammatory Response to Exhaustive Exercise in Relation to Oxidative Stress

Abstract: Exhaustive exercise induces systemic inflammatory responses, which are associated with exercise-induced tissue/organ damage, but the sources and triggers are not fully understood. Herein, the basics of inflammatory mediator cytokines and research findings on the effects of exercise on systemic inflammation are introduced. Subsequently, the association between inflammatory responses and tissue damage is examined in exercised and overloaded skeletal muscle and other internal organs. Furthermore, an overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 125 publications
(300 reference statements)
4
140
0
7
Order By: Relevance
“…Whilst regular physical exercise has many health benefits, these beneficial effects can be reversed with intense/exhaustive exercise. As such, depending on the intensity and duration of exercise, it may cause muscle and/or organ damage [ 78 ]. During acute and/or exhaustive exercise, inflammatory cells such as neutrophils and macrophages infiltrate into injured tissues and can, therefore, reduce exercise performance and increase fatigue and soreness.…”
Section: Effects Of Sfn On Exercise-induced Organ Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Whilst regular physical exercise has many health benefits, these beneficial effects can be reversed with intense/exhaustive exercise. As such, depending on the intensity and duration of exercise, it may cause muscle and/or organ damage [ 78 ]. During acute and/or exhaustive exercise, inflammatory cells such as neutrophils and macrophages infiltrate into injured tissues and can, therefore, reduce exercise performance and increase fatigue and soreness.…”
Section: Effects Of Sfn On Exercise-induced Organ Damagementioning
confidence: 99%
“…Exercise increases blood supply in muscle tissue, but excessive production of ROS causes hypoperfusion of other internal organs, and results in organ damage. Production of cytokines, chemokines, and damage-associated molecular patterns (DAMPs) are increased in the damaged cells, which enhances migration of leukocytes to the damaged tissues and causes further damage [ 78 ]. In this regard, SFN is an active antioxidant to prevent muscle and internal organ damage ( Figure 2 ).…”
Section: Effects Of Sfn On Exercise-induced Organ Damagementioning
confidence: 99%
“…These aspects highlight the necessity of staying as active as possible during 2019-nCoV quarantine period. Exercise has long been recognized as an important mediator of inflammatory processes which could suppress or reinforce the immune system (Batatinha et al, 2019;Suzuki, 2019;Suzuki et al, 2020). Some studies have suggested that the effect of exercise training on the immune system shows a doseresponse relationship, meaning that training variables could determine the effects (Batrakoulis et al, 2019).…”
Section: General Recommendation On Physical Activitiesmentioning
confidence: 99%
“…In fact, under oxidative stress, Nrf2 within the nucleus interacts with antioxidant responsive element (ARE), leading to cell survival. However, under hemostatic conditions, Nrf2 binds to the suppressor of the keap1 protein in the cytoplasm and is thus targeted by ubiquinine-dependent degradation in the proteasome [125,126]. On the other hand, many studies have recently concluded that Nrf2 can play an effective role in the prevention and treatment of diseases including exercise-induced organ damage and inflammation [122,123,126].…”
Section: Antioxidant Supplements As a Pro-oxidantmentioning
confidence: 99%